Hypereosinophilia in a boy with asthma and Varicella Zoster Virus infection - Varini, Margherita; Rinaldi, Laura; Bonetti, Lorenza; Neri, Fabiola; Santamaria, Francesca; Stringari, Giovanna; Caffarelli, Carlo (Acta Biomedica Atenei Parmensis, 2014)
Hypereosinophilia is a rare pediatric condition that could be secondary to infections, allergens, immunologic disorders or may be expression of a clonal proliferation. We report the case of an asthmatic boy aged 9 years who presented hypereosinophilia with spontaneous resolution. He had positive serum IgM antibodies to Varicella Zoster Virus while other tests, including genetic ones, gave negative results. Our findings suggest that in children with unexplained hypereosinophilia Varicella Zoster Virus infection should be investigated.